2014
DOI: 10.3109/10826084.2014.850309
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Affective Mechanisms Linking Trait Mindfulness to Craving Among Individuals in Addiction Recovery

Abstract: The present study aimed to identify affective, cognitive, and conative mediators of the relation between trait mindfulness and craving in data culled from an urban sample of 165 persons (in abstinence verified by urinalysis) entering into residential treatment for substance use disorders between 2010 and 2012. Multivariate path analysis adjusting for age, gender, education level, employment status, and substance use frequency indicated that the association between the total trait mindfulness score on the Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 66 publications
0
44
0
1
Order By: Relevance
“…Then the adapted drug craving items were summed with the alcohol craving items to compute a total substance craving score across all 10 items (α = .93). This substance craving version of the PACS has been validated in several studies (Garland & Roberts-Lewis, 2013; Garland, Roberts-Lewis, Kelley, Tronnier, & Hanley, 2014; Witkiewitz & Bowen, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Then the adapted drug craving items were summed with the alcohol craving items to compute a total substance craving score across all 10 items (α = .93). This substance craving version of the PACS has been validated in several studies (Garland & Roberts-Lewis, 2013; Garland, Roberts-Lewis, Kelley, Tronnier, & Hanley, 2014; Witkiewitz & Bowen, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Cross-sectional research indicates that reappraisal mediates the association between dispositional mindfulness and depressive symptoms among patients with psychiatric disorders (Desrosiers, Vine, Klemanski, & Nolen-Hoeksema, 2013). Relatedly, among patients with substance use disorders, the inverse association between trait mindfulness and craving was partially mediated by positive reappraisal (Garland, Roberts-Lewis, Kelley, Tronnier, & Hanley, 2014). Moreover, in the largest cross-sectional study of this phenomenon to date (N = 819), across five diverse samples including college students, alcohol dependent adults, and chronic pain patients, trait mindfulness was correlated with positive reappraisal (r = .41), even after controlling for positive affect (Hanley & Garland, 2014).…”
Section: Evidence For a Link Between Mindfulness And Positive Reappramentioning
confidence: 99%
“…A quasi-experimental study found that relative to college students in a standard communications class, students in a mindful communication course had significantly greater increases in dispositional mindfulness which were coupled with enhanced positive reappraisal (Huston, Garland, & Farb, 2011). Cross-sectional research indicates that reappraisal mediates the association between dispositional mindfulness and depressive symptoms among treatment-seeking patients with psychiatric disorders (Desrosiers, Vine, Klemanski, & Nolen-Hoeksema, 2013), and mediates the association between mindfulness and craving among persons with substance dependence (Garland, Roberts-Lewis, Kelley, Tronnier, & Hanley, in press). In laboratory research employing an experimental sadness induction, persons who had completed Mindfulness-Based Cognitive Therapy demonstrated significantly greater reappraisal efficacy than persons who had been treated with cognitive-behavioral therapy or a matched, untreated control group (Troy, Shallcross, Davis, & Mauss, 2012).…”
Section: Introductionmentioning
confidence: 99%